Extending the individual level of virtuality: Implications of task virtuality in virtual and traditional settings - Mehmet A. Orhan (Administrative Sciences, 2014)
Virtuality in organizations has usually been treated as a characteristic that is observed either at a team or organizational level. However, the penetration of new technologies into our lives has transformed the entire design of organizations and teams. Not only has the design of teams and organizations changed, but the context and design of our jobs have also been impacted. Today, even employees in traditional team settings use electronic communication tools to work with multiple dispersed contacts outside of their teams and organizations, such as colleagues, clients or suppliers, who do not share the same geographical location. With all of these changes, virtuality can no longer be considered as a concept that is exclusive to virtual team members. In today's organizations, to some extent, everyone's tasks involve non-face-to-face contacts, irrespective of team virtuality. It therefore becomes crucial to identify the task virtuality phenomenon in organizations. With this paper, the example of Yahoo! is used as a case study to illustrate how task virtuality can be relevant for the design of organizations. Additionally, the proposed two-dimensional framework integrates both team virtuality and task virtuality elements in organizations. This framework is novel in that it not only allows us how to conceptualize the task virtuality, but also provides practical guidance for managers to identify and understand the factors leading to high task virtuality and to deal with the resulting complexities.
Keywords: 350; task virtuality; individual level of virtuality; team virtuality; organizational design